Catalyst for preparing synthesis gas through low-temperature methane catalytic partial oxidation and preparation method of catalyst

By embedding isolated single atomic sites on the mesoporous nanosphere support, the problem that existing catalysts require high temperatures to maintain high activity is solved, and the catalytic partial oxidation of low-temperature methane is achieved, reducing energy consumption and maintaining high conversion rates.

CN119425682APending Publication Date: 2025-02-14DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411555034.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing methane-catalyzed partial oxidation catalysts need to maintain high activity at higher temperatures, resulting in high energy consumption and harsh reaction conditions.

Method used

The HTLAD strategy is used to synthesize mesoporous nanosphere carriers with high specific surface area and completely embedded in isolated single atomic sites on it. The presence of stable N coordination forms promotes the breakage of C-H bonds in methane molecules, thereby achieving the catalytic part of low-temperature methane. Oxidation.

Benefits of technology

The catalytic partial oxidation of methane is achieved at a temperature below the current industrial reaction (400-500°C), reducing the reaction energy consumption and maintaining a methane conversion rate of more than 30%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of nano material preparation, and discloses a catalyst for preparing synthesis gas through low-temperature methane catalytic partial oxidation and a preparation method of the catalyst. A catalyst for preparing synthesis gas through low-temperature methane catalytic partial oxidation comprises an active component and a carrier, the active component is a precious metal element, and the carrier is a cerium oxide-Lewis base mesoporous nanosphere synthesized through an HTLAD strategy; wherein the isolated monatomic sites are completely embedded into the mesoporous nanospheres. The separated monatomic sites exist in a stable N coordination form, so that breakage of C-H bonds in methane molecules is promoted, and methane catalytic partial oxidation can be carried out at a relatively low temperature. The prepared catalyst has good reaction performance and long service life, can catalyze partial oxidation of methane at the temperature lower than the current industrial reaction temperature, and reduces the reaction energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation, and particularly relates to a catalyst for preparing synthesis gas by catalytic partial oxidation of methane at low temperature and a preparation method thereof. Background Art

[0002] Natural gas is a mixture of low-carbon hydrocarbons and non-hydrocarbons, of which methane (CH4) is the main component, accounting for more than 90%. Using methane to produce high-value-added chemical products is one of the important ways to increase the added value of natural gas. At present, methane is mainly converted through two ways: one is the direct conversion method, which directly oxidizes methane, selectively partially oxidizes to produce alcohols, aldehydes, and oxygen-free aromatization to produce aromatic hydrocarbons. Another method is to first convert methane into synthesis gas (carbon monoxide (CO) and hydrogen (H2)), and then carry out subsequent chemical processes. The indirect conversion method has a higher utilization rate and relatively mature supporting processes, and has become the main process for methane conversion. The methods for preparing synthesis gas from methane through indirect conversion methods include methane steam reforming, methane carbon dioxide dry reforming, methane partial oxidation, autothermal reforming, etc. As a weak exothermic reaction, the catalytic partial oxidation of methane is milder in terms of reaction conditions and has lower energy consumption than the reforming reaction. In addition, the carbon-hydrogen ratio of the product is 1:2, which is conducive to subsequent reactions such as Fischer-Tropsch synthesis.

[0003] The methane partial oxidation catalysts with good effects that have been reported at this stage can be divided into four categories according to the active components: (1) non-precious metal catalysts (Ni, Co, etc.); (2) precious metal catalysts (Ru, Rh, Pd, Pt, etc.); (3) composite metal catalysts (Ni-Co, Pt-Ru, Ni-Pt, Ni-Ru, etc.); (4) metal oxide catalysts (LaCoO3, LaNi 1-x Co x O3, LaNiO3, etc.).

[0004] However, most of the existing catalysts need to be at a higher temperature to maintain high activity. In 2007, Journal of Catalysis reported the Rh / Al2O3 catalyst prepared by R. Horn et al., which achieved a methane conversion rate of 37% in 6 vol% CH4, but required a higher reaction temperature (1000°C). In 2015, International Journal of Hydrogen Energy reported the Co–Ni–Ru catalyst prepared by Halit Eren Figen et al., which could achieve a methane conversion rate of 98% at 850°C. In 2018, Boukha et al. reported their synthesized Rh / HAP catalyst in Applied Catalysis A: General. The catalyst has good stability, but the reaction needs to be above 700°C. Chinese patent CN 1785516A discloses a catalyst for catalytic partial oxidation of methane to produce synthesis gas and its preparation method, the catalyst group is a supported alumina catalyst, the active component of which is one of Ru, Rh, Pd, and Pt, and the catalyst is used at a temperature of 800-1000°C. Therefore, further developing low-temperature, efficient and stable catalysts and realizing their industrialization is one of the main directions of current research on catalytic partial oxidation of methane. Summary of the invention

[0005] The present invention provides a catalyst for preparing synthesis gas by catalytic partial oxidation of methane at low temperature and a preparation method thereof. The method adopts the HTLAD strategy to construct a mesoporous nanosphere carrier with a high specific surface area, wherein isolated single atomic sites are completely embedded in the mesoporous nanosphere. The isolated single atomic sites exist in a stable N-coordinated form, promoting the breaking of the CH bond in the methane molecule, so that the catalytic partial oxidation of methane can be carried out at a lower temperature.

[0006] The technical solution of the present invention:

[0007] A catalyst for preparing synthesis gas by catalytic partial oxidation of methane at low temperature comprises an active component and a carrier, wherein the active component is a noble metal element and the carrier is a cerium oxide-Lewis base mesoporous nanosphere synthesized by the HTLAD strategy; wherein the Lewis base is used as an anchoring point to anchor the active metal.

[0008] Based on the percentage of the mass of active metal in the catalyst to the mass of the carrier, the content of the active component is 0.5% to 6%.

[0009] A method for preparing a catalyst for preparing synthesis gas by catalytic partial oxidation of methane at low temperature comprises the following steps:

[0010] (1) Ce(NO3)2 was used as a raw material to synthesize cerium dioxide nanoparticles with an average diameter of 10-40 nm by a hydrothermal method; a polymer monomer was added to deionized water containing cerium dioxide nanoparticles, and a hydrochloric acid solution was added dropwise to adjust the pH, and the mixture was stirred at room temperature for 1-3 hours;

[0011] (2) adding ammonium persulfate solution to the above solution, standing at room temperature, polymerizing for 12-36 hours to obtain cerium oxide-polymer core-shell nanoparticles, and washing with deionized water and ethanol several times;

[0012] (3) adding ammonia water to the obtained cerium oxide-polymer core-shell nanoparticles, adjusting the pH, and stirring for 6-24 hours to deprotonate; after stirring, collecting the solid, washing it with deionized water, then washing it with solution A several times, and drying it overnight; pyrolyzing the deprotonated nanoparticles under an inert gas flow at 600-800° C. for 1-6 hours to obtain cerium oxide-Lewis base core-shell composite nanoparticles, which are sealed for later use;

[0013] (4) A noble metal salt solution is added to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare a precursor by an impregnation method; the precursor is first calcined in an oxidizing atmosphere at 400-600° C. for 2-6 hours, and then reduced in a reducing atmosphere at 300-500° C. to obtain the catalyst.

[0014] The polymer monomer in step (1) is one or a combination of two or more of urea-formaldehyde resin, polyamide-66, nitrile rubber, polyamide-1010, nylon-610, polyacrylamide, polyaniline, and poly-N-vinyl caprolactam.

[0015] The concentration of the hydrochloric acid solution in step (1) is 1-3M, and the pH is adjusted to 1-3;

[0016] The concentration of the ammonium persulfate solution in step (2) is 1-1.5M, and the molar ratio of the polymer monomer to the ammonium persulfate is controlled to be 1:50-1:200;

[0017] The concentration of the ammonia water in step (3) is 0.8-1.2M, and the pH is adjusted to 9-12;

[0018] The solution A in step (3) is at least one of nitrobenzene, nitromethane, chloroform, dimethylamine aqueous solution, and dimethyl sulfoxide; the molar ratio of solution A to polymer monomer is 1:10-1:100;

[0019] The noble metal in step (4) is at least one of Ru, Rh, Pd, Ir and Pt; the noble metal salt is at least one of nitrate, sulfate, chloride and acetate of the noble metal;

[0020] The oxidizing gas in step (4) comprises oxygen and argon, and the volume ratio of oxygen to argon is 1:50-1:20.

[0021] An application of the above catalyst in catalytic partial oxidation of methane is characterized in that the catalyst can carry out atmospheric catalytic partial oxidation of a CH4 / O2 / N2 (molar ratio of 9 / 3 / 8, flow rate of 30 mL / min) mixed gas at 400-500°C through a continuous injection fixed bed reactor to prepare synthesis gas.

[0022] Beneficial effects of the present invention:

[0023] 1. The low-temperature methane catalytic partial oxidation catalyst prepared by the present invention has a mesoporous structure, which can greatly increase the specific surface area, thereby greatly increasing the surface active sites;

[0024] 2. The high specific surface area and thin pore wall of the catalyst fully expose all isolated single active metal atoms, and its mesoporous structure is conducive to mass transfer and activation of methane molecules;

[0025] 3. The prepared catalyst has good reaction performance and long service life. It can catalyze the partial oxidation of methane at a temperature lower than the current industrial reaction temperature, thereby reducing the reaction energy consumption. DETAILED DESCRIPTION

[0026] Example 1

[0027] 1. Synthesize cerium dioxide nanoparticles with an average diameter of 20 nm by hydrothermal method;

[0028] 2. Add 0.4 g of urea-formaldehyde resin monomer to 100 mL of distilled water containing 1.6 g of cerium oxide nanoparticles, drop 1.2 M hydrochloric acid aqueous solution into the prepared solution until pH = 3, and stir for 1 hour.

[0029] 3. Add 1 M ammonium persulfate aqueous solution to the solution obtained in 2. Polymerize the urea-formaldehyde resin at room temperature for 12 h, centrifuge after polymerization to obtain cerium oxide-urea-formaldehyde resin core-shell nanoparticles, and wash with deionized water and ethanol several times.

[0030] 4. Add 50 mL of 1M ammonia water to the cerium oxide-urea-formaldehyde resin core-shell nanoparticles obtained in 3 and stir for 12 hours to deprotonate. After stirring, collect the solid, wash it with deionized water, wash it with nitromethane several times, and dry it overnight. The deprotonated nanoparticles are pyrolyzed at 800°C under an inert gas flow for 3 hours to finally obtain cerium oxide-Lewis base core-shell composite nanoparticles.

[0031] 5. Add 1.6 ml of 10 mg / mL RuCl3 solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare the precursor by impregnation. The precursor was first calcined at 550 ° C in an oxygen-argon (1 / 49) atmosphere for 4 h, and then reduced at 300 ° C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-1.

[0032] Example 2

[0033] 1. Synthesize cerium dioxide nanoparticles with an average diameter of 20 nm by hydrothermal method;

[0034] 2. Add 0.4 g of polyacrylamide monomer to 100 mL of distilled water containing 1.6 g of cerium oxide nanoparticles, drop 1.2 M hydrochloric acid aqueous solution into the prepared solution until pH = 3, and stir for 1 hour.

[0035] 3. Add 1 M ammonium persulfate aqueous solution to the solution obtained in 2. Polyacrylamide was polymerized at room temperature for 12 h, and centrifuged after polymerization to obtain cerium oxide-polyacrylamide core-shell nanoparticles, which were washed several times with deionized water and ethanol.

[0036] 4. Add 50 mL of 1M ammonia water to the cerium oxide-polyacrylamide core-shell nanoparticles obtained in 3 and stir for 12 hours to deprotonate. After stirring, collect the solid, wash it with deionized water, wash it with nitromethane several times, and dry it overnight. The deprotonated nanoparticles are pyrolyzed at 800°C under an inert gas flow for 3 hours to finally obtain cerium oxide-Lewis base core-shell composite nanoparticles.

[0037] 5. Add 1.6 ml of 10 mg / mL RuCl3 solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare the precursor by impregnation. The precursor was first calcined at 550 ° C in an oxygen-argon (1 / 49) atmosphere for 4 h, and then reduced at 300 ° C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-2.

[0038] Example 3

[0039] 1. Synthesize cerium dioxide nanoparticles with an average diameter of 20 nm by hydrothermal method;

[0040] 2. Add 0.4 g of polyamide-66 monomer to 100 mL of distilled water containing 1.6 g of cerium oxide nanoparticles, drop 1.2 M hydrochloric acid aqueous solution into the prepared solution until pH = 3, and stir for 1 hour.

[0041] 3. Add 1 M ammonium persulfate aqueous solution to the solution obtained in 2. Polyamide-66 was polymerized at room temperature for 12 h, and centrifuged after polymerization to obtain cerium oxide-polyamide-66 core-shell nanoparticles, which were washed several times with deionized water and ethanol.

[0042] 4. Add 50 mL of 1M ammonia water to the cerium oxide-polyamide-66 core-shell nanoparticles obtained in 3 and stir for 12 hours to deprotonate. After stirring, collect the solid, wash it with deionized water, wash it with nitromethane several times, and dry it overnight. The deprotonated nanoparticles are pyrolyzed at 800°C under an inert gas flow for 3 hours to finally obtain cerium oxide-Lewis base core-shell composite nanoparticles.

[0043] 5. Add 1.6 ml of 10 mg / mL RuCl3 solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare the precursor by impregnation. The precursor was first calcined at 550 ° C in an oxygen-argon (1 / 49) atmosphere for 4 h, and then reduced at 300 ° C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-3.

[0044] Example 4

[0045] 1. Synthesize cerium dioxide nanoparticles with an average diameter of 20 nm by hydrothermal method;

[0046] 2. Add 0.4 g of polyaniline monomer to 100 mL of distilled water containing 1.6 g of cerium oxide nanoparticles, drop 1.2 M hydrochloric acid aqueous solution into the prepared solution until pH = 3, and stir for 1 hour.

[0047] 3. Add 1 M ammonium persulfate aqueous solution to the solution obtained in 2. Polymerize aniline at room temperature for 12 h, centrifuge after polymerization to obtain cerium oxide-polyaniline core-shell nanoparticles, and wash with deionized water and ethanol several times.

[0048] 4. Add 50 mL of 1M ammonia water to the cerium oxide-polyaniline core-shell nanoparticles obtained in 3 and stir for 12 hours to deprotonate. After stirring, collect the solid, wash it with deionized water, wash it with nitromethane several times, and dry it overnight. Pyrolyze the deprotonated nanoparticles at 800°C under an inert gas flow for 3 hours to finally obtain cerium oxide-Lewis base core-shell composite nanoparticles.

[0049] 5. Add 1.6 ml of 10 mg / mL RhCl3 solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare the precursor by impregnation. The precursor was first calcined at 550 ° C in an oxygen-argon (1 / 49) atmosphere for 4 h, and then reduced at 300 ° C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-4.

[0050] Example 5

[0051] 1. Synthesize cerium dioxide nanoparticles with an average diameter of 20 nm by hydrothermal method;

[0052] 2. Add 0.4 g of aniline monomer to 100 mL of distilled water containing 1.6 g of cerium oxide nanoparticles, drop 1.2 M hydrochloric acid aqueous solution into the prepared solution until pH = 3, and stir for 1 hour.

[0053] 3. Add 1 M ammonium persulfate aqueous solution to the solution obtained in 2. Polymerize aniline at room temperature for 12 h, centrifuge after polymerization to obtain cerium oxide-polyaniline core-shell nanoparticles, and wash with deionized water and ethanol several times.

[0054] 4. Add 50 mL of 1M ammonia water to the cerium oxide-polyaniline core-shell nanoparticles obtained in 3 and stir for 12 hours to deprotonate. After stirring, collect the solid, wash it with deionized water, wash it with nitromethane several times, and dry it overnight. Pyrolyze the deprotonated nanoparticles at 800°C under an inert gas flow for 3 hours to finally obtain cerium oxide-Lewis base core-shell composite nanoparticles.

[0055] 5. Add 1.6 ml of 10 mg / mL RuCl3 solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare the precursor by impregnation. The precursor was first calcined at 550 ° C in an oxygen-argon (1 / 49) atmosphere for 4 h, and then reduced at 300 ° C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-5.

[0056] Example 6

[0057] 1. Synthesize cerium dioxide nanoparticles with an average diameter of 20 nm by hydrothermal method;

[0058] 2. Add 0.4 g of aniline monomer to 100 mL of distilled water containing 1.6 g of cerium oxide nanoparticles, drop 1.2 M hydrochloric acid aqueous solution into the prepared solution until pH = 3, and stir for 1 hour.

[0059] 3. Add 1 M ammonium persulfate aqueous solution to the solution obtained in 2. Polymerize aniline at room temperature for 12 h, centrifuge after polymerization to obtain cerium oxide-polyaniline core-shell nanoparticles, and wash with deionized water and ethanol several times.

[0060] 4. Add 50 mL of 1M ammonia water to the cerium oxide-polyaniline core-shell nanoparticles obtained in 3 and stir for 12 hours to deprotonate. After stirring, collect the solid, wash it with deionized water, wash it with nitromethane several times, and dry it overnight. Pyrolyze the deprotonated nanoparticles at 800°C under an inert gas flow for 3 hours to finally obtain cerium oxide-Lewis base core-shell composite nanoparticles.

[0061] 5. Add 0.8 ml of 10 mg / mL RuCl3 solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare the precursor by impregnation. The precursor was first calcined at 550 ° C in an oxygen-argon (1 / 49) atmosphere for 4 h, and then reduced at 300 ° C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-6.

[0062] Example 7

[0063] 1. Synthesize cerium dioxide nanoparticles with an average diameter of 20 nm by hydrothermal method;

[0064] 2. Add 0.4 g of aniline monomer to 100 mL of distilled water containing 1.6 g of cerium oxide nanoparticles, drop 1.2 M hydrochloric acid aqueous solution into the prepared solution until pH = 3, and stir for 1 hour.

[0065] 3. Add 1 M ammonium persulfate aqueous solution to the solution obtained in 2. Polymerize aniline at room temperature for 12 h, centrifuge after polymerization to obtain cerium oxide-polyaniline core-shell nanoparticles, and wash with deionized water and ethanol several times.

[0066] 4. Add 50 mL of 1M ammonia water to the cerium oxide-polyaniline core-shell nanoparticles obtained in 3 and stir for 12 hours to deprotonate. After stirring, collect the solid, wash it with deionized water, wash it with nitromethane several times, and dry it overnight. Pyrolyze the deprotonated nanoparticles at 800°C under an inert gas flow for 3 hours to finally obtain cerium oxide-Lewis base core-shell composite nanoparticles.

[0067] 5. Add 3.2 ml of 10 mg / mL RuCl3 solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare the precursor by impregnation. The precursor was first calcined at 550°C in an oxygen-argon (1 / 49) atmosphere for 4 h, and then reduced at 300°C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-7.

[0068] Example 8

[0069] Weigh 500 mg of commercial CeO2 carrier, add 0.5 ml of 10 mg / mL RuCl3 solution and 10 ml of deionized water, stir until dry, grind to obtain a precursor. The precursor was calcined in a muffle furnace with a heating rate of 5 ° C / min, calcined at 550 ° C for 4 h, cooled to room temperature, moved into a tubular furnace, and reduced at 300 ° C for 2 h in a hydrogen atmosphere. The obtained catalyst was recorded as C-8.

[0070] Example 9

[0071] Weigh 500 mg of commercial Al2O3 carrier, add 0.5 ml of 10 mg / mL RhCl3 solution and 10 ml of deionized water, stir until dry, grind to obtain a precursor. The precursor was calcined in a muffle furnace with a heating rate of 5 °C / min, calcined at 550 °C for 4 h, cooled to room temperature, moved into a tubular furnace, and reduced at 300 °C in a hydrogen atmosphere for 2 h. The obtained catalyst was recorded as C-9.

[0072] Application conditions

[0073] The catalyst of the present invention reacts in a continuous sampling fixed bed quartz reactor, the reaction temperature is 400°C, the raw gas composition is CH4 / O2 / N2=9 / 3 / 8 (molar ratio), the flow rate is 30ml / min, and the product is analyzed online by gas chromatography after condensation and dehydration. Sampling and analysis began after 30 minutes of reaction, and the evaluation results are shown in Table 1.

[0074] Table 1 Catalyst reaction performance

[0075] catalyst Methane conversion rate (%) CO selectivity (%) <![CDATA[H2 Selectivity (%)]]> C-1 9.3 13.1 58.4 C-2 11.9 12.0 43.8 C-3 8.0 10.7 12.2 C-4 12.0 44.8 50.1 C-5 31.2 72.3 92.9 C-6 10.5 15.5 47.2 C-7 11.7 14.1 49.6 C-8 6.8 18.2 37.6 C-9 5.7 32.6 67.7 <![CDATA[Commercial Rh / Al2O3]]> 3.4 16.3 30.1 <![CDATA[Commercial Ni / Al2O3]]> 3.1 8.5 12.6

[0076] Through experimental tests, the low-temperature methane catalytic partial oxidation catalyst prepared by the present invention can react (400-500°C) to produce synthesis gas at a temperature lower than the current industrial methane catalytic partial oxidation temperature (700-900°C), and can maintain a methane conversion rate of more than 30%. Compared with the currently reported commercial catalysts, the present catalyst has higher activity in the low temperature region and has more advantages.

Claims

1. A catalyst for preparing synthesis gas by catalytic partial oxidation of methane at low temperature, characterized in that: The synthesis gas catalyst comprises an active component and a carrier, wherein the active component is a noble metal element, and the carrier is a cerium oxide-Lewis base mesoporous nanosphere synthesized by the HTLAD strategy; wherein the Lewis base is used as an anchoring point to anchor the active metal; and based on the percentage of the mass of the active metal in the catalyst to the mass of the carrier, the content of the active component is 0.5% to 6%.

2. A method for preparing a catalyst for preparing synthesis gas by catalytic partial oxidation of methane at low temperature, characterized in that: The steps include: (1) Ce(NO3)2 was used as a raw material to synthesize cerium dioxide nanoparticles with an average diameter of 10-40 nm by a hydrothermal method; a polymer monomer was added to deionized water containing cerium dioxide nanoparticles, and a hydrochloric acid solution was added dropwise to adjust the pH, and the mixture was stirred at room temperature for 1-3 hours; (2) adding ammonium persulfate solution to the above solution, standing at room temperature, polymerizing for 12-36 hours to obtain cerium oxide-polymer core-shell nanoparticles, and washing with deionized water and ethanol several times; (3) adding ammonia water to the obtained cerium oxide-polymer core-shell nanoparticles, adjusting the pH, and stirring for 6-24 hours to deprotonate; after stirring, collecting the solid, washing it with deionized water, then washing it with solution A several times, and drying it overnight; pyrolyzing the deprotonated nanoparticles under an inert gas flow at 600-800° C. for 1-6 hours to obtain cerium oxide-Lewis base core-shell composite nanoparticles, which are sealed for later use; (4) adding a noble metal salt solution to the cerium oxide-Lewis base core-shell composite nanoparticles to prepare a precursor by an impregnation method; The precursor is first calcined in an oxidizing atmosphere at 400-600° C. for 2-6 hours, and then reduced in a reducing atmosphere at 300-500° C. to obtain a synthesis gas catalyst.

3. The preparation method according to claim 2, characterized in that: The polymer monomer in step (1) is one or a combination of two or more of urea-formaldehyde resin, polyamide-66, nitrile rubber, polyamide-1010, nylon-610, polyacrylamide, polyaniline, and poly-N-vinyl caprolactam; and the molar ratio of cerium oxide to the polymer monomer is 1:50-1:

200.

4. The preparation method according to claim 2, characterized in that: The concentration of the hydrochloric acid solution in step (1) is 1-3M, and the pH is adjusted to 1-3.

5. The preparation method according to claim 2, characterized in that: The concentration of the ammonium persulfate solution in step (2) is 1-1.5M, and the molar ratio of the polymer monomer to the ammonium persulfate is controlled to be 1:50-1:

200.

6. The preparation method according to claim 2, characterized in that: The concentration of the ammonia water in step (3) is 0.8-1.2 M, and the pH is adjusted to 9-12.

7. The preparation method according to claim 2, characterized in that: The solution A in step (3) is at least one of nitrobenzene, nitromethane, chloroform, dimethylamine aqueous solution, and dimethyl sulfoxide; the molar ratio of solution A to polymer monomer is 1:10-1:

100.

8. The preparation method according to claim 2, characterized in that: The noble metal in step (4) is at least one of Ru, Rh, Pd, Ir and Pt; the noble metal salt is at least one of nitrate, sulfate, chloride and acetate of the noble metal.

9. The preparation method according to claim 2, characterized in that: The oxidizing gas in step (4) comprises oxygen and argon, and the volume ratio of oxygen to argon is 1:50-1:

20.

10. Use of the synthesis gas catalyst according to claim 1 in catalytic partial oxidation of methane, characterized in that: The catalyst can perform atmospheric pressure catalytic partial oxidation of the mixed gas at a molar ratio of CH4, O2 and N2 of 9:3:8 and a flow rate of the mixed gas of 30 mL / min at 400-500°C through a continuous injection fixed bed reactor to prepare synthesis gas.

Citation Information

Patent Citations

  • Catalyst for making synthetic gas from methane by catalyzing partly oxidation and its preparation method

    CN1785516A